Narcisizem pri porodnicah - Slana, Mojca (Psihološka obzorja (Ljubljana), 2010)
The aim of this study was to determine, whether there are any, and if so, which differences there are in narcissism in puerperium between first-time mothers, third-time mothers and women, who have never been pregnant. There were 170 women participants, divided into three groups. The first group consisted of 71 first-time mothers and the second group of 21 third-time mothers. In the third, comparative, group there were 78 women, who have never been pregnant. The participants completed the questionnaire Narzißmusinventar (Deneke and Hilgenstock, 1989). The results showed no significant differences between both groups of mothers. Significant differences in narcissism were present mainly only between first-time mothers and the comparative group. They suggest lower narcissism of the group of the first-time mothers.
Keywords: narcizem; porodnice